PSVI-12 Phosphorous digestibility of corn ethanol co-products, from Brazil and USA, in growing pigs - Paula, Vinicius R C (J Anim Sci, 2020)
The objective of this study was to determine the apparent total tract digestibility (ATTD) and the standardized total tract digestibility (STTD) of P, and their respective digestible values, of two high protein (HP) corn dried distillers’ grains (DDG) and of two corn DDG with solubles (DDGS), from Brazil and USA, in pigs. Fifty crossbred barrows (38.3±5.2kg BW) were fed a semi-purified P-free basal diet (BD), used to determine endogenous P losses, or four diets composed of 40% of each ingredient, as the only source of P, substituting for starch in BD: Brazilian HP DDG (BHP); USA HP DDG (UHP); Brazilian DDGS (BDG) and USA DDGS (UDG). Animals were fed at 2.8 x maintenance (110 kcal of DE per kg of BW0.75) for 9 d (7 d adaptation and 2 d of partial feces collection). Titanium dioxide was used as an indigestible marker (0.3%) for digestibility calculations. A randomized block design was used, with 10 replicates, using the pig as the experimental unit. Results were submitted to ANOVA and Tukey’s test (P< 0.05). The ATTD of P of UHP and UDG were 47% greater (P< 0.05) than those verified in BHP and BDG. The STTD of P of UHP and UDG were 45% higher (P < 0.05) than that of BDG. The STTD of BHP was similar (P >0.05) to the values of BDG and UDG. The total and standardized digestible P of UDG (0.40-0.44%, respectively) were greater (P< 0.05) than those of BDG (0.33-0.38 %, respectively) and of UHP (0.28-0.32%, respectively), which were similar (P > 0.05), and higher than that of BHP (0.22-0.27%, respectively). In conclusion, corn distiller’s co-products from Brazil and USA presented different ATTD and STTD P values, and USA DDGS (UDG) showed the highest apparent total tract and standardized digestible P among all corn coproducts evaluated. [Image: see text]